2019
DOI: 10.1097/sih.0000000000000334
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality Future Step Visualization for Robust Surgical Telementoring

Abstract: Surgical telementoring connects expert mentors with trainees performing urgent care in austere environments. However, such environments impose unreliable network quality, with significant latency and low bandwidth. We have developed an augmented reality telementoring system that includes future step visualization of the medical procedure. Pregenerated video instructions of the procedure are dynamically overlaid onto the trainee's view of the operating field when the network connection with a mentor is unreliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…And then Canada is following USA in terms of researches performed on the same [18,20,24,43]. And when the research methods used in the studies were examined, it was observed that literature review [8,9,10,13,14,19,33,34,36,40], compilation and AR practices applied on surgical operations were published at a high degree [17,18,20,24,26,35,44]. (Graph 2) When the fields of application of AR, used in trainings provided in the domain of health, were examined, it is being observed by Graph 3 that it was used the most in the medical education [5,7,8,11,14,22,36,40,43].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…And then Canada is following USA in terms of researches performed on the same [18,20,24,43]. And when the research methods used in the studies were examined, it was observed that literature review [8,9,10,13,14,19,33,34,36,40], compilation and AR practices applied on surgical operations were published at a high degree [17,18,20,24,26,35,44]. (Graph 2) When the fields of application of AR, used in trainings provided in the domain of health, were examined, it is being observed by Graph 3 that it was used the most in the medical education [5,7,8,11,14,22,36,40,43].…”
Section: Resultsmentioning
confidence: 99%
“…(Graph 2) When the fields of application of AR, used in trainings provided in the domain of health, were examined, it is being observed by Graph 3 that it was used the most in the medical education [5,7,8,11,14,22,36,40,43]. When articles on AR practices used in surgical sciences were examined, it was observed that the highest number of publications was on the domain of General Surgery as clinical domain [13,17,20,44]. And when the key words of the publications were analyzed, it is being observed by Graph 5 that the most frequently used key word was "Augmented Reality" [5,7,8,9,11,13,14,15,16,17,19,20,21,22,23,26,27,29,31,33,34,35,37,38,39,41,42,44,45,46], and the second one was "Virtual Reality" [ 8,9,13,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Systems accessing the wireless network also need to deal with poor wireless connectivity attributed to the absence of the wireless signal coverage, the weakness of the signal, or the incompatibility between the wireless system and the AR system. In one experiment, Andersen et al (2019) suggested that a future step in visualisation could be a backup mechanism in case of poor network connectivity. For example, before the experiment, the steps of the procedure or performance task could be audio-recorded, and then during the experiment, users could switch between the live instruction provided by the mentor in real time and the instruction recorded previously and stored in the device.…”
Section: Discussionmentioning
confidence: 99%
“…Another problem is that telementoring systems are highly dependent on the telecommunications systems used. As such, the reliability of those systems affects the mentoring process and thus potentially the operative outcome (30), and very few systems can reliably overcome connectivity challenges through fail-safe modes (31). Verbal instruction by the mentor is crucial to telementoring; however, noise in the operating room can interfere with the mentor's audio communication to the extent that the operating surgeon must wear a headset (32).…”
Section: Fundamental Challenges In Telementoring Interventional/surgical Proceduresmentioning
confidence: 99%